XVIII. Yüzyılda Yazılmış Hülle Konulu Bir Mesnevi: Vasık-Zade Re'fet Efendi ve Hülle-Name'si - (:unkn) unknown (My University, 2006)
Hülle, üç talâkla boşanmış bir kadının ayrıldığı kocasına tekrar dönebilmesi için bir başka erkekle evlenmesini ifade eder. Böyle evliliğe tahlîl denir. Hülle-nâme’nin yazarı Re’fet, XVIII. yüzyılda yaşamış bir divan şairidir. Ailesi Madrub-zâdeler olarak bilinir. Babası Vâsık Efendi ile kardeşi Erşed Efendi de şairdir. Re’fet’in Hülle-nâme’si şimdiki bilgilerimize göre hülle konusunda yazılmış en eski edebî eserdir. Mesnevî nazım şekli ile, aruzun cedîd bahrinin feilâtün mefâilün feilün kalıbıyla kaleme alınmıştır ve 156 beyittir. Hülle-nâme, yaşanmış, gerçek bir olaya dayanmaktadır.

Hulla means interim marriage necessary before a divorced couple can remarry. A man marries a divorced woman on condition of divorcing her in a very short time so that she can remarry her previous husband. Hulla-nama was written by Re’fet Efendi living in the 18th century. He is a Ottoman poet just like his father Vâsik Efendi and brother Ershed Efendi. It is known that the Hulla-nama of Re’fet Efendi is the oldest literary work about interim marriage. Its meter is aruz cadid fa’ilâtun mefâ’ilun fa’ilun. It has 156 couplets. Its subject is a real event.
A Matnavı (Masnawı) Written in the 18th Century on Interim Marriage: Vasık-Zada Re'fet Efendi and His Hulla-Nama
Keywords: Antropoloji